DETERMINANTS OF INTERNAL AND EXTERNAL FACTORS OF NON – PERFORMING LOANS OF LOCAL COMMERCIAL BANKS - Syed Yousaf Hassan; Dr. Hakim Ali Mahesar; Usman Masood (International Journal of Contemporary Issues in Social Sciences, 2024)
The Banks play a major role in fostering the economic well-being of a State. Their basic objective is to bridge the gap between the people who have surplus funds and the ones who have the scarcity of funds. The role of financial institutions as financial intermediaries is well established and is highly regulated throughout the world. After the financial turmoil of 2008 which was triggered due to the non-performing mortgages loans of US and had a spill over affect throughout the world. The regulators as well as the researchers have focused on the menace of non-performing loans in order to unveil the factors which should be curtailed in order to avoid any such situation in the future. This study analyzed the bank internal factors and bank external factors which had an impact on the Non-Performing Loans (NPL). The objective was to provide the factors which significantly influence the non-performing loans and such elements can be controlled by the Bank’s management. The impact of ROA, SIZE, CAR (Capital Adequacy Ratio) and Ownership concentration with a level of more than 10%, 25% and 50% and external factor INFLATION, UN EMPLOYEMENT and PUBLIC DEBT was analyzed by using Fixed Effect Method and the validity was tested by Hausman test. Data of 17 Pakistani Commercial Banks and economic variables which was gathered for the period 2010-2016. The results revealed that the ROA, SIZE and CAR have a significant and negative impact on the non-performing loans. It was also observed that ownership concentration more than 10% and less than 25% was significant but was inversely related to the NPLs.